Problematika dan Tantangan Organisasi Informasi Perpustakaan di Abad 21: Studi di UPT Perpustakaan UM - Novianto, Achmad Qorni; Mas'ud, Ali (LIBTECH: LIBRARY AND INFORMATION SCIENCE JOURNAL, 2024)
Abstract Technological developments in the 21st century present various changes in library management, including information organization activities in libraries. The organization of library information is closely related to the information retrieval process in the library. Limited human resources available, technological developments, the increasing number of collections that must be processed every year are certainly problems that must be faced by the UM Library UPT. In this research, a library study approach was used, which is a type of research that utilizes various library sources related to information organization activities carried out at the UM Library UPT. The problems and challenges of information organization at the UM Library UPT consist of (1) the presence of tools for digital era library materials, (2) determining the subject headings of library materials and their role in the information retrieval process, (3) processing digital collections, (4) the urgency of developing UM Integrated Information System (SIPADU UM), and (5) competency development and additional human resources processing library materials. Keywords: library; library, information organization, SIPADU  AbstrakPerkembangan teknologi di abad 21 menyajikan berbagai perubahan dalam tata kelola perpustakaan, tak terkecuali kegiatan organisasi informasi di perpustakaan. Organisasi informasi perpustakaan sangat erat kaitannya dengan proses temu kembali informasi di perpustakaan. Terbatasnya sumber daya manusia yang tersedia, perkembangan teknologi, bertambah banyaknya koleksi yang harus diolah setiap tahunnya tentu menjadi problematika yang harus dihadapi oleh UPT Perpustakaan UM. Dalam riset ini, digunakan pendekatan studi kepustakaan, yang merupakan jenis penelitian yang memanfaatkan berbagai sumber kepustakaan dikaitkan dengan kegiatan organisasi informasi yang dilaksanakan di UPT Perpustakaan UM. Problematika dan tantangan organisasi informasi pada UPT Perpustakaan UM terdiri atas (1) kehadiran alat bantu bahan pustaka era digital, (2) penentuan tajuk subjek bahan pustaka dan perannya dalam proses temu kembali informasi, (3) pengolahan koleksi digital, (4) urgensi Pengembangan Sistem Informasi Terpadu UM (SIPADU UM), dan (5) pengembangan kompetensi dan penambahan SDM pengolah bahan pustaka. Kata Kunci: perpustakaan, organisasi informasi, SIPADU